Psychological Well Being pada Penderita Obesitas dengan Penggunaan Media Sosial Berlebihan: Implikasi dalam Konteks Pendidikan Kesehatan: Penelitian - Yoza Okta Saputra; Danny Ontario Rusmono; Ahmad Fauzan Iswahyudi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
In the modern era, lifestyle issues such as obesity are exacerbated by excessive social media use. Excessive social media use tends to decrease physical activity, disrupt sleep patterns, increase late-night eating habits, and encourage the consumption of unhealthy foods widely promoted online. Obesity and excessive social media use both significantly impact psychological well-being. This study aims to explore the psychological well-being of individuals with obesity who use social media excessively, a phenomenon that has not been widely studied simultaneously. The study used purposive sampling with data analysis through open coding, axial coding, and selective coding, and validity testing through triangulation and peer debriefing. The results showed low psychological well-being of participants, particularly in aspects of self-acceptance, personal growth, life purpose, and autonomy, reflected in low self-confidence, unclear life goals, and lack of independence in decision-making.